Cardiovascular disease during the COVID-19 pandemic: Think ahead, protect hearts, reduce mortality - Li, Guoliang (Cardiol J, 2020)
Coronavirus disease 2019 (COVID-19) is rapidly spreading globally. As of October 3, 2020, the number of confirmed cases has been nearly 34 million with more than 1 million fatalities. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is accountable for COVID-19. Newly diagnosed and worsening cardiovascular disease are common complications in COVID-19 patients, including acute cardiac injury, hypertension, arrhythmia, myocardial infarction, heart failure and sudden cardiac arrest. The mechanisms contributing to cardiac disease burden include hypoxemia, inflammatory factor storm, dysfunctional angiotensin converting enzyme 2 (ACE2), and drug-induced cardiac toxicity. Notably, the macrophages expressing ACE2 as direct host cells of SARS-CoV-2 secrete chemokine and inflammatory cytokines, as well as a decrease in cellular immune responses to SARS-CoV-2 infection due to elevated exhaustion levels and dysfunctional diversity of T cells, that may be accountable for the “hyperinflammation and cytokine storm syndrome” and subsequently acute cardiac injury and deteriorating cardiovascular disease in COVID-19 patients. However, no targeted medication or vaccines for COVID-19 are yet available. The management of cardiovascular disease in patients with COVID-19 include general supportive treatment, circulatory support, other symptomatic treatment, psychological assistance as well as online consultation. Further work should be concentrated on better understanding the pathogenesis of COVID-19 and accelerating the development of drugs and vaccines to reduce the cardiac disease burden and promote the management of COVID-19 patients, especially those with a severe disease course and cardiovascular complications.